Tingkat Self Compassion pada Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Sanata Dharma yang Mengalami Toxic Relationship Berpacaran - Jending Yola Pratiwi Pamanda; Bernardinus Agus Arswimba (Jurnal Kajian dan Penelitian Umum, 2024)
This research aims to: (1) Find out the level of self-compassion in students at the Faculty of Teacher Training and Education, Sanata Dharma University who experience toxic relationships in dating. (2) Find out which items on the self-compassion scale are still less than optimal, which will later be used as a proposal for a guidance program. This type of research is quantitative descriptive. The subjects in the research conducted were students at the Faculty of Teacher Training and Education, Sanata Dharma University who experienced toxic dating relationships. Data collection used a self-compassion scale with 36 valid items with a Cronbach Alpha reliability index of 0.910. The scale is prepared based on 3 aspects, namely self-kindness, common humanity and mindfulness. The data analysis technique used in this research is descriptive statistics, using the SPSS version 22 application. The majority of self-compassion results for Sanata Dharma University FKIP students who experienced toxic dating relationships were moderately dominant. The results of the research conducted showed that out of 31 students, as many as 6.5% of students who experienced a toxic relationship had a very high level of self-compassion, 16.1% of students who experienced a toxic relationship in a relationship had a high level of self-compassion, 38.7% of students those who experienced a toxic dating relationship had a moderate level of self-compassion, 35.5% of students who experienced a toxic dating relationship had a low level of self-compassion, and 3.2% of students who experienced a toxic dating relationship had a very low level of self-compassion. There are 16 items measuring self-compassion which were identified as having low scores and 3 items measuring self-compassion which were identified as having very low scores which were proposed as guidance topics.